Portuguese Physical Literacy Assessment for adolescents (15-18 years): validation using confirmatory factor and composite analyses - João Mota; João Mota; João Mota; João Martins; João Martins; Marcos Onofre; Marcos Onofre; Dean Dudley; Dean Dudley; Dean Dudley (Frontiers Media S.A., 2023)
ObjectiveThe aim of this study was to assess the construct validity and reliability of the Portuguese Physical Literacy Assessment (PPLA) instruments (a questionnaire and a tool using teacher-reported data). We also investigated the conceptual and practical implications of reflective vs. formative measurement of Physical Literacy using the PPLA.MethodsMultiple Confirmatory Factor Analysis (CFA) and Confirmatory Composite Analysis (CCA) models were used complementarily to assess construct validity in a sample of 521 grade 10-12 Portuguese students from Lisbon, Portugal. Bifactor model-based indices (ω), Explained Common Variance (ECV), and Percentage of Uncontaminated Correlations (PUC) were used to assess score reliability and adequacy.ResultsUsing CFA, an asymmetrical bifactor model (S*1-1) provided the best fit to the data [Robust Comparative Fit Index = 97, Robust Root Mean Square Error Of Approximation = 0.05 (0.04-0.06), Standardized Root Mean Square Residual (SRMR) = 0.04], while CCA resulted in the best absolute fit for single first-order composite models (dG, dL, and SRMR below or borderline of their 95% critical value). Through a reflective paradigm, the total PL score should not be used in isolation (ECV = 0.49, ωH = 0.71, lower than recommended 0.80). Subscales for the Physical, Psychological, and Social domains attained acceptable reliability scores (ωs = 0.76, 0.82, 0.80, and 0.60).ConclusionsA general trait of PL accounts for considerable variance in all indicators. We advise calculation of a total summed PL score and domain scores, which should be interpreted conjointly in applied settings. Despite both paradigms being tenable, future research efforts should use a bifactor measurement model, which permits disentanglement of the variance attributed to the general PL trait and its domains. Overall, evidence supported the construct validity and reliability of the PPLA for its intended use as an integrated tool to measure PL as a multidimensional construct in 15- to 18-year-old Portuguese students in a physical education setting.